“Sin las ollas, no hubiéramos sobrevivido”: Estado de la cuestión de la problemática social de las ollas comunes durante la pandemia del COVID-19 - Montoya Díaz, Raúl Humberto (2024)
The “ollas comunes” (CO) (“common pots”) have played an important role as essential food organizations over the past four years during the COVID-19 pandemic, serving as the primary food sources for numerous families facing difficulties during this period. The objective of this paper is to present an introductory context on the role of common pots during the pandemic. Following this, a brief overview of the state of the issue concerning community kitchens and common pots in Peru and Latin America will be presented. The methodology used in this paper was a literature review, analyzing previous research on these food organizations.